2014
DOI: 10.1002/anie.201404490
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Intermolecular Interactions for Efficient Room‐Temperature Phosphorescence from Purely Organic Materials in Amorphous Polymer Matrices

Abstract: Herein we report a rational design strategy for tailoring intermolecular interactions to enhance room-temperature phosphorescence from purely organic materials in amorphous matrices at ambient conditions. The built-in strong halogen and hydrogen bonding between the newly developed phosphor G1 and the poly(vinyl alcohol) (PVA) matrix efficiently suppresses vibrational dissipation and thus enables bright room-temperature phosphorescence (RTP) with quantum yields reaching 24%. Furthermore, we found that modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
250
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 432 publications
(260 citation statements)
references
References 22 publications
1
250
0
Order By: Relevance
“…[1][2][3][4][5][6] Until very recently, the URTP phenomenon was mostly described for inorganic or organometallic materials containing noble metals or rare-earth elements. Among those, molecules displaying ultralong room-temperature phosphorescence (URTP) are of paramount importance notably for their applications as active materials in bioimaging, anticounterfeiting, information storage, oxygen sensing, etc.…”
Section: Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Until very recently, the URTP phenomenon was mostly described for inorganic or organometallic materials containing noble metals or rare-earth elements. Among those, molecules displaying ultralong room-temperature phosphorescence (URTP) are of paramount importance notably for their applications as active materials in bioimaging, anticounterfeiting, information storage, oxygen sensing, etc.…”
Section: Thin Filmsmentioning
confidence: 99%
“…In 2017, Shoji et al revealed the exceptional phosphorescence properties of a series of simple crystalline arylboronic esters, with lifetimes up to 1.73 s, which is-to the best of our knowledge-one of the longest values ever reported for metal-free organic phosphors. [1][2][3][4][5][6] Until very recently, the URTP phenomenon was mostly described for inorganic or organometallic materials containing noble metals or rare-earth elements. After dispersion into polyvinyl alcohol (PVA) to create drop-coating thin films and long irradiation under strong UV light (65 min, 254 nm), an intense phosphorescence (Φ p up to 11.23%) associated with a long lifetime (up to 0.71 s) could be observed at room temperature in aerated atmosphere.…”
mentioning
confidence: 99%
“…39,40 Furthermore, BF 2 chelates have demonstrated the ability to restrict intramolecular twisting of the aromatic-carbonyl moiety to produce rare, metal-free phosphorescence in rigid environments. 20,4144 …”
Section: Introductionmentioning
confidence: 99%
“…The unique properties could be concentrated on ap ure organic compound through this design strategy,w hichprovides an ew efficient channel for the discovery of efficient mechanoresponsive organic materials.Controlling and tuning the solid-state luminescence of organic materials continues to be an attractive topic in both theoretical research and practical applications in the fields of sensing, [1] color displays, [2] and data storage. Following the principle of color mixing, myriad emission colors with aw ide range from orange to purple and across white zone in astraight line in the chromaticity diagram of the Commission Internationale de lEclairage (CIE) can be obtained by simply mechanical grinding the compound.…”
mentioning
confidence: 99%
“…Controlling and tuning the solid-state luminescence of organic materials continues to be an attractive topic in both theoretical research and practical applications in the fields of sensing, [1] color displays, [2] and data storage. [3] Ther elationship in the molecular level between the emission properties of organic luminescent materials and the external pressure or mechanical stimuli has recently gained considerable attention because the knowledge of such ar elationship is essential to real-world applications of the "smart" materials.…”
mentioning
confidence: 99%